Training for Workers and Safety Representatives on Manufactured Nanomaterials. (May 2019) - Castillo, Aida Ponce Del
Although nanotechnologies are increasingly present in numerous sectors of the economy, training resources available to workers exposed to them are still rare. In the European Union (EU), some initiatives exist that inform workers about exposure and risks, but they lack two key dimensions: the involvement of workers themselves in designing and implementing training materials and the key role played by safety representatives in improving occupational health and safety in EU member states. Making workers actors of their own training, rather than recipients of it, and empowering them, so that they can collectively question unsafe situations and ask for changes in their working conditions, is how training can positively impact their health and safety. This article describes a training package (materials, infographics, interactive web applet) designed specifically to achieve this objective. Developed under the NanoDiode project, it focuses on six key themes: types of nanomaterials, uses at work, risks, presence in the workplace, exposure, and experience sharing.